Primary care physicians’ perceptions of Israel’s national program for quality indicators in community healthcare– 2010 and 2020 - Rachel Nissanholtz-Gannot; Ayala Burger; Bruce Rosen (Israel Journal of Health Policy Research)
Abstract Background Monitoring the quality of primary care is essential for improving healthcare services. The National Program for Quality Indicators in Community Healthcare measures various aspects of healthcare quality. A 2010 survey among Israeli primary care physicians (PCPs) found widespread support for the program alongside concerns about its effects on workload and competitiveness. This study assessed the extent to which PCPs’ perceptions had changed between 2010 and 2020. Methods Cross-sectional survey on PCP’s experience with the quality monitoring effort at their health maintenance organizations were conducted in 2010 and 2020 among representative samples of PCPs. Bivariate analysis examined whether the study variables varied between the timepoints. Logistic regression models evaluated the extent to which the participants’ characteristics and perceptions contribute to their attitudes toward the program. Results The study sample comprised 605 physicians in 2010 and 450 physicians in 2020. Overall, support for the National Program for Quality Indicators was high in both surveys. However, between 2010 and 2020 some decrease in the support for the use of quality indicators was observed among PCPs The greatest decrease in support between 2010 and 2020 was observed in the proportion of respondents who perceived that it is important to a great or very great extent to measure the clinical performance of some quality indicators (88% versus 81%) and in the proportion of respondents who perceived that monitoring contributed to improvement (66% versus 60%). Over half of respondents (58%) perceived to a large or very large extent that the program was associated with increased workload compared to 63% in 2010. Similar proportions of respondents in 2010 and 2020 felt that the program was also associated to a large or very large extent with over-competition (47% and 48%, respectively) and excess managerial pressure (58% and 60%, respectively). Conclusions The study indicates that while support for the program in general remains high, it continues to have undesirable side effects. Further use of the program for quality indicators must consider the shortcomings voiced in 2010 which have remained uncorrected as reflected in the results of the 2020 survey: extreme managerial pressures, increased workload and over-competitiveness.